Translational regulation of the plant S-adenosylmethionine decarboxylase. (1st April 2003) - Hanfrey, C.; Franceschetti, M.; Mayer, M.J.; Illingworth, C.; Elliott, K.; Collier, M.; Thompson, B.; Perry, B.; Michael, A.J.
Abstract : It is becoming apparent that control of protein synthesis by metabolites is more common than previously thought. Much of that control is exerted at the level of initiation of mRNA translation, orchestrated by upstream open reading frames (uORFs) and RNA secondary structure. S-Adenosylmethionine decarboxylase (AdoMetDC) is a key enzyme in polyamine biosynthesis and both mammalian and plant AdoMetDCs are translationally regulated by uORFs in response to polyamine levels by distinct mechanisms.